Temporal equal and active participation in synchronous collaborative learning: Antecedents and effect for learning - Sixiong Peng; Shunsaku Komatsuzaki; Ryota Sen (PLoS ONE, 2025)
For teaching 21st century skills, collaborative learning has been increasingly adopted in educational programs nowadays. However, learners often fail to engage in effective collaboration, which severely deteriorates learning gains. To develop support tools for collaborative learning, participation is one of the promising aspects considering its effect on learning gains and its viability for real-time measurement in modern learning environments. This study quantitatively and qualitatively examined the relationship between temporal equal and active participation and learning gains in synchronous collaboration. Our data included 10 teams that collaboratively learn analogical thinking in university coursework. Our result demonstrated the positive relationship between temporal equal and active participation and team learning gains. Detailed observation revealed that equal and active participation often reflected joint information processing which in turn affected learning gains, although this relationship depends on the discussion contents. The effect could be direct, indirect or absent depending on discussion topics and other factors. Our comparative analysis also proposed three antecedents for equal and active participation; maintaining a shared understanding of what to discuss and why to discuss, critical comments for extending discussion, and arguing without completion. We lastly summarized our theoretical implications for equal and active participation and practical implications for supporting collaborative learning.